Survey Of Physical Fitness Players of SSB Karlos Malang, Aged 15 Years - Nailahya Arriza Shofan (Indonesian Conditioning Coaches, 2024)
The aim of the researcher is to assess the level of physical fitness of the 15-year-old SSB Karlos Malang soccer school players with the TKJI test instrument for the 13-15 year age category. The researcher uses this type of quantitative descriptive research using survey techniques. The results of the TKJI test conducted on 15 subjects showed that there were 0 (0%) subjects who were in the